DYNAMIC OF PARANOID SYNDROMES IN SCHIZOPHRENIA IN DEPENDENCE ON DELUSIONS OF BEING CONTROLLED - Stefan Todorov; Mariana Arnaoudova; Koralia Todorova (Journal of IMAB, 2011)
Delusions of being controlled are psychotic symptoms among the most characteristic symptoms of schizophrenia. The aim of our study was to explore the dynamic of paranoid syndromes in schizophrenia in dependence on delusions of outside control. The objects were 160 schizophrenic patients, aged 18-65 years. We distinguished, conditionally, three consecutive, but not obligatory stages in the syndrome dynamic. The first stage is characterized by sense of “loss of Ego-control” on separate psychic functions, not engaged with a concrete outside influence. On the second stage the sense of “loss of Ego-control” concretizes and forms delusional conception of outside influence and control. On the third stage Ego-control of one’s own psychic processes is replaced by delusional conviction of outside control. A total depersonalization in the frame of paranoid syndrome is observed.The clinical peculiarities of each stage of paranoid syndromes in dependence on the delusions of influence testify, to some extent, to one or other progression of schizophrenic process and could have a relatively prognostic value.